On a Cave containing Bones and Objects of Human Workmanship, at Borness, Kirkcudbrightshire - Corrie, Adam J; Bruce-Clarke, William; Hunt, Arthur R (Proceedings of the Society of Antiquaries of Scotland, 1875)